Unusual microbiological presentations in polymicrobial post-operative endophthalmitis and their clinical correlations - Mitra, Sanchita; Padhi, Tapas Ranjan; Basu, Soumyava; Priyadarshini, Smruti Rekha; Sharma, Savitri (International ophthalmology, 2019)
Purpose To report the clinical course, microbiological spectrum and visual outcomes of three cases of post-operative endophthalmitis caused by unusual combination of micro-organisms. Methods Retrospective review of medical charts at a tertiary eye care centre over a period of 1 year, of subjects with post-operative endophthalmitis and more than one microbiological isolate. Results We report 3 cases with unusual combination of microorganisms. In case 1, two organisms ( Burkholderia cepacia and Aeromonas veronii , from the vitreous cavity and capsular bag, respectively ) with an identical antibiotic sensitivity pattern were found, while in case 2, the organisms ( Streptococcus pneumoniae and Sphingomonas paucimobilis , from cornea and vitreous cavity, respectively ) isolated had different sensitivity patterns. In case 3, two different strains of the same organism ( Enterococcus faecalis) were found. Cases 1 and 2 achieved good anatomical and visual outcomes, while in case 3, vision remained poor despite a good anatomical outcome. Conclusion Unusual combinations of organisms in post-operative endophthalmitis can introduce unique clinical characteristics and should specifically be considered in atypical clinical presentations, poor response to standard therapy and unusual recurrence patterns.